2017
DOI: 10.1049/iet-map.2016.1084
|View full text |Cite
|
Sign up to set email alerts
|

Multiband monopole antenna with minimised ground plane influence for portable devices

Abstract: A multiband monopole antenna with minimised ground plane influence for portable devices is presented. This antenna operates at LTE band 13 (0.746–0.787 GHz), GPS, LTE band 11 (1.427–1.495 GHz), LTE band 3 (1.71–1.88 GHz), WLAN (2.4–2.48 GHz) and WiMAX (3.3–3.88 GHz) with at least −6 dB of reflection coefficient. The performance of antennas for portable devices is commonly influenced by the ground plane to result in variation in terms of operating frequency, impedance bandwidth and radiation pattern. Via a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Many promising antennas with multiband characteristics for wireless operations have been reported in the past decade 1–19 . In Fei et al, 1 a dualband printed compound loop antenna consisted of a small inner rectangular ring, an outer rectangular loop and a parasitic strip to operate in 2.4/5 GHz of WLAN and 3.5 GHz of WiMAX bands have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Many promising antennas with multiband characteristics for wireless operations have been reported in the past decade 1–19 . In Fei et al, 1 a dualband printed compound loop antenna consisted of a small inner rectangular ring, an outer rectangular loop and a parasitic strip to operate in 2.4/5 GHz of WLAN and 3.5 GHz of WiMAX bands have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…From Table 5, it can be observed that the proposed antenna has the following features: Unlike to all existing state of arts, 1‐24 the proposed antenna is simple in design, compact and has dimensions of only 6 × 4 mm 2 , thus it can reduce the space required for mounting the antenna inside an actual laptop computers. Unlike those reported in References 16, 18, 19, the proposed antenna can operate within the desired bands of interest without using any additional lumped elements (inductors, capacitors etc. ), 3‐D structures and added holes or vias. Compared with References 1–5, 8, 9, 16, 18–20 the proposed antenna is suitable for different sizes of laptops and other portable devices. Unlike References 8, 9, 18, and the proposed antenna has exhibited broader fractional impedance bandwidths of 6.5% and 16% across the two operating bands. Compared with those in References 1, 4, 5, 11, 14, 21, 23, and the gain of the proposed antenna is above 3 dBi across all the operating bands. The proposed antenna can cover both the fundamental 2.4 and 5 GHz bands, unlike References 1–3, 7, 12. The proposed antenna does not require additional ground plane for affixing the antenna to system ground, unlike Reference 11 Unlike References 4, 5, 13, and the proposed antenna does not use expensive substrate. …”
Section: Performance Comparison Of Proposed Antenna With Other Pioneementioning
confidence: 98%
“…From the available open-literature, extensive research work has been carried out on antenna miniaturization in terms of novel structures and antenna performances. To accommodate the demand for rapid development in wireless laptop applications, 1 proposed a monopole antenna comprising of spiral loop strips, stub, and ground plane. However, the overall size of the spiral main radiating element is 18.6 × 20 mm, and thus it is unattractive for modern portable thin laptops.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Industrial Scientific Medical (ISM) bands, namely 2.4 GHz (2.40-2.48) GHz and 5 GHz (5.15-5.85) GHz are used in the WLAN/WiMAX environment. Therefore, multiband antennas including inverted-F [1,2], the coupled-fed planar inverted-F antennas in [3,4], branched monopole antenna [5], dual band monopole antenna [6], printed antenna [7], monopole antennas using reactive components [8,9], antennas using additional ground plane [10,11], meander antennas [12,13], folded antennas [14,15], uniplanar antennas in [16,17,18,19], broadband antenna [20], antennas having thickness of 1 mm [21,22,23,24] and cloverleaf-shaped monopole antenna [25] have been reported recently for WLAN/WiMAX technologies for the laptop computers. From the above mentioned antennas, it is understood that miniaturized and ultra-thin antennas showing high performance with less complex structure and covering WLAN/WiMAX bands for laptop applications are posing challenges for antenna designers due to shrinking of height and thickness of outside frame of the laptop display.…”
Section: Introductionmentioning
confidence: 99%